Antibacterial and In Vitro Growth Inhibition Study of Struvite Urinary Stones Using Oxalis corniculata Linn. Leaf Extract and its Biofabricated Silver Nanoparticles - Das, Poppy; Kumar, Kiran; Nambiraj, Arunai; Awasthi, Rajendra; Dua, Kamal; Malipeddi, Himaja (Recent Patents on Drug Delivery & Formulation, 2018)
Background: Herbal drugs are gaining exponential scientific recognition due to their distinct advantages. In the last 2-3 decades, a gradual increase in worldwide patents on herbal nanoformulations has been noted to address the solubility and bioavailability issues of phytoceuticals. Struvite or ammonium magnesium phosphate hexahydrate (NH4MgPO4.6H2O) is among the important urinary infection stones causing painful urological ailment. These smaller stones may bind together to form bigger staghorn calculus. Urinary tract infections caused by some gram positive and gram negative bacteria further enhance the chance of formation of such stones. Oxalis corniculata Linn. is an edible plant, traditionally used in the treatment of bacterial infections and kidney stones. However, there is no scientific evidence to relate the use of O. corniculata against struvite kidney stones. Hence, the antibacterial and struvite stones inhibition activity of the aqueous extract of Oxalis corniculata Linn. leaves and its biofabricated silver nanoparticles (AgNPs) was studied. Methods: The aqueous extract of O. corniculata was prepared by Soxhlet extraction. AgNPs were synthesized using green technique and were characterized using UV and IR spectroscopy, XRD, TEM, DLS and zeta potential studies. Antibacterial activity of the aqueous extract and the silver nanoparticles was tested against E. coli (gram negative) and S. aureus (gram positive) species. Struvite stones were grown in a gel medium by in vitro single diffusion gel growth technique and its inhibition study was carried out using the extract and its biofabricated nanoparticles. Results: The aqueous extract and its biofabricated AgNPs exhibited potent antibacterial activity against both gram positive and gram negative strains of bacteria. The aqueous extract also effectively repressed the growth of struvite stones and led to the dissolution of stones, but the inhibitory effect was further enhanced by its biofabricated AgNPs. Conclusion: The present work confirms the inhibitory activity of the aqueous extract of edible O. corniculata and its biofabricated silver nanoparticles against urinary tract infection (UTI) causing bacteria and urolithiasis. Therefore, the consumption of O. corniculata in our daily diet may reduce the risk of UTI and urolithiasis.
Keywords: silver nanoparticles